Environmental Management as a Strategic Capability: a Study on the Furniture Manufacturing Cluster of Southern Brazil - Janielen Pissolatto Deliberal; Vilmar Antonio Gonçalves Tondolo; Maria Emília Camargo; Rosana da Rosa Portella Tondolo (BBR: Brazilian Business Review)
The incorporation of company programs aimed at sustainability strategies contributes to a balance between economic growth and the use of natural resources. This issue is not exclusive for companies from developed markets. Companies from emerging markets also need to find a way to achieve sustainable practices and organizational performance at the same time. In this context, the aim of this study was to analyze whether environmental management can be considered as a strategic capability, contributing positively to the performance of the manufacturing companies belonging to the Furniture Manufacturing Cluster of Southern Brazil (FMCSB). In order to achieve our objective, we performed a quantitative study through a survey. The sample collected data from 162 companies. Based on univariate and multivariate analysis the results suggest that environmental management can be considered as a strategic capability for the FMCSB since environmental practices are significantly related to organizational performance.